2022
DOI: 10.4018/jeco.300302
|View full text |Cite
|
Sign up to set email alerts
|

Fear of Coronavirus on Continuance Intention to Use Food Delivery Apps

Abstract: The objective of this research is to explore the determinants impacting the Indian consumers’ continuance intention (CI) to use food delivery app (FDA) during the Covid-19 pandemic. The study develops a conceptual framework which integrates technology acceptance model (TAM) and expectation confirmation model (ECM), with fear of Coronavirus (FOC) and health anxiety (HA). The survey responses of 598 FDA users during Covid-19 pandemic period in India were examined using PLS – SEM approach. The findings reveal tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 77 publications
(87 reference statements)
1
1
0
Order By: Relevance
“…For example, Roh and Park (2019) found significant impacts of both PU and PEOU on individuals' intention to use online‐to‐offline food delivery services. Moreover, during the COVID‐19 pandemic, the same results were found by Lee et al (2023) and Raman (2022), who reported that PU and PEOU significantly positively influenced the intention to use food delivery applications. These findings highlighted the importance of considering both PU and PEOU when examining users' behavioral intentions toward OFD services.…”
Section: Literature Review and Hypothesis Developmentsupporting
confidence: 80%
See 1 more Smart Citation
“…For example, Roh and Park (2019) found significant impacts of both PU and PEOU on individuals' intention to use online‐to‐offline food delivery services. Moreover, during the COVID‐19 pandemic, the same results were found by Lee et al (2023) and Raman (2022), who reported that PU and PEOU significantly positively influenced the intention to use food delivery applications. These findings highlighted the importance of considering both PU and PEOU when examining users' behavioral intentions toward OFD services.…”
Section: Literature Review and Hypothesis Developmentsupporting
confidence: 80%
“…These findings highlighted the importance of considering both PU and PEOU when examining users' behavioral intentions toward OFD services. In addition, previous studies found a positive association between ease of use and usefulness when using OFD services (Lee et al, 2023;Raman, 2022;Roh & Park, 2019). For instance, Roh and Park (2019) and Lee et al (2023) found that users' PEOU toward OFD services had a strong impact on their PU.…”
Section: Research Model and Hypothesis Developmentmentioning
confidence: 90%